Angiopoietin-2 is a negative prognostic marker in small cell lung cancer. Issue 2 (November 2015) - Cañadas, Israel; Taus, Álvaro; Villanueva, Xavier; Arpí, Oriol; Pijuan, Lara; Rodríguez, Yara; Menéndez, Silvia; Mojal, Sergi; Rojo, Federico; Albanell, Joan; Rovira, Ana; Arriola, Edurne
Graphical abstract: Highlights: Circulating angiogenesis-related cytokines were quantified in SCLC patients. Angiopoietin-2 serum levels significantly increase during the course of the disease. High Angiopoietin-2 serum levels are associated with poor outcome in SCLC patients. Angiopoietin-2 serum levels can serve as a useful prognostic marker in SCLC. Circulating Angiopoietin-2 may be a potential therapeutic target in this disease. Abstract: Background: Small cell lung cancer (SCLC) is a highly lethal disease due to its chemorefractory nature after initial treatment. Angiogenesis plays an important role in tumor growth, metastasis and chemoresistance. We hypothesized that angiogenesis could predict chemoresistance in SCLC patients and be potentially a therapeutic target in this disease. Methods: Serum samples from forty-three SCLC patients were prospectively obtained at diagnosis, response evaluation and progression. Angiogenesis-related cytokines (Angiopoietin-2, VEGF-A, C and D) were simultaneously quantified by Luminex Technology. Clinical data were prospectively recorder. Results: Significantly higher concentration of angiogenesis-related cytokines were found in SCLC patients at diagnosis compared to healthy volunteers. High baseline serum concentration of Angiopoietin-2 (sAngiopoietin-2) were associated with a worse overall survival ( p  = 0.006) and remained independently associated with survival in the multivariate analysis ( p  = 0.008). In addition, sAngiopoietin-2 significantly increased at progression when compared to baseline. Conclusion: These data provide novel evidence on a role of sAngiopoietin-2 in the adverse clinical behavior of SCLC and could be a potential therapeutic target in this disease.